2013
DOI: 10.1007/s12350-012-9659-x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardium at risk: Reasons and methods for measuring the extent

Abstract: See related article, pp. 99-110 MYOCARDIUM AT RISKIf a coronary artery is acutely occluded, the downstream myocardium becomes severely under-perfused and at risk of necrosis. The area of myocardium at jeopardy of infarction is usually referred to as area at risk. It is intuitive that the extent of myocardium at risk downstream from an occluded coronary artery does not have the dimension of an area, but rather that of a volume or a mass. Indeed, the extent of myocardium at risk is usually expressed in grams or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similarly, a limitation of infarct size was observed after administration of JWH133 ( Yu et al, 2019 ) and HU308 ( Wang et al, 2012 ) after AMI. One should keep in mind, that myocardial infarction is properly expressed as percentage of the area at risk which represents the myocardial perfusion bed distal to an occluded artery ( Gimelli and Rovai, 2013 ; Heusch, 2019 ). Unfortunately, the reduction in infarct size in cannabinoid studies (Tables 3 - 5 ) was not correlated with the reduction of the area at risk (with one exception in the study of Liu et al (2021) .…”
Section: Cardioprotection In Experimental Myocardial Ischemia/reperus...mentioning
confidence: 99%
“…Similarly, a limitation of infarct size was observed after administration of JWH133 ( Yu et al, 2019 ) and HU308 ( Wang et al, 2012 ) after AMI. One should keep in mind, that myocardial infarction is properly expressed as percentage of the area at risk which represents the myocardial perfusion bed distal to an occluded artery ( Gimelli and Rovai, 2013 ; Heusch, 2019 ). Unfortunately, the reduction in infarct size in cannabinoid studies (Tables 3 - 5 ) was not correlated with the reduction of the area at risk (with one exception in the study of Liu et al (2021) .…”
Section: Cardioprotection In Experimental Myocardial Ischemia/reperus...mentioning
confidence: 99%
“…In the setting of acute coronary syndromes and acute myocardial infarction, it was a well-accepted fact that patients with chronic coronary artery disease and longlasting anginal symptoms could attain better response to primary percutaneous interventions, as it was demonstrated by more limited infarct size according to enzymatic measurements, cardiac magnetic resonance, and myocardial perfusion imaging. 1 In particular, the importance of collaterals in possibly preserving tissue during acute myocardial infarction was proven by means of myocardial perfusion imaging. 2 Thus, it was suggested that coronary collateral circulation could explain the protective role of previous history of stable angina and therefore an assessment of its extent could in theory be helpful to explain part of the variability of the final treatment results that can range from infarct abortion to an extensive myocardial damage.…”
mentioning
confidence: 99%
“…2 Thus, it was suggested that coronary collateral circulation could explain the protective role of previous history of stable angina and therefore an assessment of its extent could in theory be helpful to explain part of the variability of the final treatment results that can range from infarct abortion to an extensive myocardial damage. 1,3 However, other studies suggested that the role of collaterals is not crucial, and it is overcome by many other parameters, such as time delay and pre-treatment TIMI flow. 4,5 Moreover, this is not a fundamental issue in the clinical practice since the therapeutic strategy remains in any case to achieve revascularization as early as possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation